Penalty for violating the professional companies system in the Saudi system: A comparative study - Moafa, Mahmoud Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
System of Professional Companies is considered one of the modern matters of concern to a large category of professionals, and due to the absence of a previous scientific study, and owing to the significance of the subject, this study aimed to demonstrate the penalty for violating the system of professional companies in legal system of Saudi Arabia (Comparative Study), between the law in the legal system of Saudi Arabia and Islamic jurisprudence The researcher followed the descriptive comparative approach, with a focus on the penalty for violating the provisions of the system of professional companies, as it is in fact in the system approved by the Saudi government and comparing it with Islamic jurisprudence to demonstrate its compatibility with Islamic law (Islamic Sharia). The study concluded that in defining the penalty we find that it includes, in the system of professional companies, for a worldly penalty, in contrast to Islamic jurisprudence, which has arranged for a worldly penalty and a hereafter penalty, and that the system of professional companies, in imposing a financial fine on the violator, is consistent with the doctrine of the majority of jurists. The study recommended severe proposals including: The legislator shall stipulate the penalty for not obtaining coverage insurance and the legislator must take care of the community’s conditions and what is appropriate for its interests.